REKAYASA PERANGKAT LUNAK BERBASIS SUMBER TERBUKA UNTUK MEMBANTU PELAKSANAAN AUDIT SISTEM INFORMASI - Husni, Hari Setiabudi (Bina Nusantara University, 2010)
This research was conducted on one budget period in 2009 funded by DIKTI young lecturer research project grant. The main research location is Bina Nusantara University. Due to tight research schedule, it was necessary to take some strategic steps to fulfill research goals. One of the strategic steps was to invite several experts in software industry to give advices regarding open source software engineering issues. The first achievement was findings of some open source software that could assist on auditing information systems. Afterwards, comparison from technical and functional aspects resulted in the best software to be tested for implementation and usage, namely ZenossCore. The final output of this research is successful reengineering of the source code for virtual file testing.Keywords: open source software, audit implementation, information system